1923
DOI: 10.1084/jem.38.2.183
|View full text |Cite
|
Sign up to set email alerts
|

Conditions Determining the Transplantability of Tissues in the Brain

Abstract: In confirmation of Shirai's observation, we find that transplantable mouse tumors grow actively when inoculated into the brains of rats, guinea pigs, and pigeons, whereas subcutaneous or intramuscular grafts in the same animals fail. This growth of foreign tissue in the brain, however, takes place only when the grafted material lies entirely in the brain tissue; if it comes in contact with the ventricle a cellular reaction takes place with resultant destruction of the graft. The growth of foreig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
82
0
1

Year Published

1964
1964
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 209 publications
(84 citation statements)
references
References 3 publications
1
82
0
1
Order By: Relevance
“…In the early years of the twentieth century, Murphy and Sturm (202) proposed two possible explanations: (i) mechanical impediment of cells to migrate beyond the perivascular spaces; (ii) lymphoid cells find the brain tissue an uncongenial environment. These authors were the first to define BBB as an ''anatomic barrier that restricts diapedesis'' and ensures the immune privileged state of the brain.…”
Section: Bbb Permeability Is Altered By Ros Enabling Homing Ofmentioning
confidence: 99%
“…In the early years of the twentieth century, Murphy and Sturm (202) proposed two possible explanations: (i) mechanical impediment of cells to migrate beyond the perivascular spaces; (ii) lymphoid cells find the brain tissue an uncongenial environment. These authors were the first to define BBB as an ''anatomic barrier that restricts diapedesis'' and ensures the immune privileged state of the brain.…”
Section: Bbb Permeability Is Altered By Ros Enabling Homing Ofmentioning
confidence: 99%
“…Back then, Y Shirai observed that rat sarcoma grew well when transplanted into the mouse brain parenchyma, but not when implanted subcutaneously or intramuscularly [2]. Murphy and Strum extended these findings in 1923 by demonstrating that if recipient spleen was cotransplanted with the foreign tumour in the brain parenchyma, it inhibited the tumour growth [3]. This showed that the survival of the foreign tumour within the brain parenchyma was occurring as a result of disconnection from the systemic immune system.…”
Section: Immune Privilege Down the Agesmentioning
confidence: 99%
“…Murphy, J.B., et al [59] have studied mouse sarcoma tissue, which was found not to be rejected implantation into rat brain and given their views that the CNS was exempt from the immunological processes responsible for graft rejection. Sabin, F.R.…”
Section: Introductionmentioning
confidence: 99%